KDEON WK-11: A short antipseudomonal peptide with promising potential - Casciaro, Bruno; Loffredo, Maria Rosa; Cappiello, Floriana; O’Sullivan, Niamh; Tortora, Carola; Manzer, Rizwan; Karmakar, Sougata; Haskell, Alan; Hasan, Syed K.; Mangoni, Maria Luisa (Frontiers in Chemistry, 2022)
The plight of antimicrobial resistance continues to limit the availability of antibiotic treatment effective in combating resistant bacterial infections. Despite efforts made to rectify this issue and minimise its effects on both patients and the wider community, progress in this area remains minimal. Here, we de-novo designed a peptide named KDEON WK-11, building on previous work establishing effective residues and structures active in distinguished antimicrobial peptides such as lactoferrin. We assessed its antimicrobial activity against an array of bacterial strains and identified its most potent effect, against Pseudomonas aeruginosa with an MIC value of 3.12 μM, lower than its counterparts developed with similar residues and chain lengths. We then determined its anti-biofilm properties, potential mechanism of action and in vitro cytotoxicity. We identified that KDEON WK-11 had a broad range of antimicrobial activity and specific capabilities to fight Pseudomonas aeruginosa with low in vitro cytotoxicity and promising potential to express anti-lipopolysaccharide qualities, which could be exploited to expand its properties into an anti-sepsis agent.